Longitudinal changes in home food availability and concurrent associations with food and nutrient intake among children at 24-48 months - Jennifer M Barton; Arden L McMath; Stewart P Montgomery; Sharon M Donovan; Barbara H Fiese (Cambridge University Press, 2024)
Abstract Objectives: To describe changes in home food availability during early childhood, including modified, developmentally sensitive obesogenic scores, and to determine whether home food availability is associated with food and nutrient intakes of children concurrently, over time. Design: Data were drawn from the STRONG Kids 2 longitudinal, birth cohort to achieve the study objectives. Home food availability was assessed with the Home Food Inventory (HFI) and included fifteen food groups (e.g. fruit and vegetables) and three obesogenic scores (one original and two modified). Food and nutrient intakes were measured using the Block FFQ and included twenty-seven food groups and eighteen nutrients (e.g. vitamins A and C, protein). HFI and FFQ were completed by trained researchers or mothers, respectively, at 24, 36 and 48 months. Repeated-measures ANOVA and Spearman's correlations were used to achieve the study objectives. Setting: Central Illinois, USA. Participants: Participants were 468 children at 24, 36 and 48 months of age. Results: Availability of less nutritious foods and obesogenic foods and beverages increased as children aged, and availability of both nutritious and less nutritious foods were associated with child food and nutrient intake. The three obesogenic scores demonstrated similar, positive associations with the intake of energy, saturated fat, added sugars and kilocalories from sweets. Conclusion: These findings offer novel insight into changes in home food availability and associations with food and nutrient intake during early childhood. Additional attention is needed examining antecedents (e.g. built environments, purchasing behaviours) and consequences (e.g. child diet quality and weight) of home food availability.